Analysis of methane gas content in cattle manure waste for electricity generation - Azfar Fadillah (PT Pustaka Intelektual Sutajaya, 2026)
This study investigates the methane (CH4) content generated through the anaerobic fermentation of cattle manure waste in a biogas digester, in support of biogas-based electricity generation development in Indonesia. A qualitative approach with a case study strategy was employed, conducted through direct field observation. The digester used was a floating dome/balloon-type unit with a slurry capacity of 300 liters, fed with 25 kg of fresh cattle manure. Primary data collected included measurements of methane gas content, hourly gas production volume, substrate pH values, and digester temperature profiles over a 10-day observation period. A comparative analysis was performed between two treatment conditions: a digester supplemented with EM4 (Effective Microorganism 4) liquid inoculant and a control digester without EM4 addition. Results indicated that the average digester temperature during the observation period was 34.18°C, which falls within the optimal mesophilic range. The measured substrate pH ranged from 6.0 to 6.7, slightly below the optimum range of 6.8–8.0 for biogas production. The floating dome digester construction was demonstrated to be capable of maintaining the anaerobic conditions required for methane gas formation.